Application of Bamboo Plants in Nine Aspects - Abolghassem Emamverdian; Yulong Ding; Fatemeh Ranaei; Zishan Ahmad (The Scientific World Journal)
Bamboo forests are undoubtedly one of the most abundant nontimber plants on Earth and cover a wide area of tropical and subtropical regions around the world. This amazing plant has unique rapid growth and can play an important role in protecting our planet from pollution and improving the soil. Bamboo can be used as a biofuel, food, and for architecture and construction applications and plays a large role in the local economy by creating job opportunities. The aim of this paper is to review the extraordinary tropical plant bamboo by explaining the mechanisms related to the growth and strength of bamboo and identifying ways to utilize bamboo in industry, employment, climate change mitigation, and soil erosion reduction.